Processes of Language Teaching and Language Learning in the Interactions of Mother-Child Dyads - Moerk, Ernst L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This study focuses on the significance of specific maternal language teaching techniques in the early language development of the child. A recording was made of the verbal and nonverbal interactions in 20 mother-child dyads during a one-hour session in the home. The linguistic level for each of the children, who ranged from 1.9 to 5.0 years in age, was computed from the average length of utterance, and the stream of verbal actions was divided into verbal episodes. These episodes, comprising one or several utterances of each interaction partner which are temporally contiguous, meaningfully related, and form a structural whole, formed the basic unit of analysis. Results indicate that mothers actively teach all aspects of language and that the interactional structures employed in the course of this teaching encompass feedback cycles and calibration processes. The mother-child dyad is described as a self-regulating and relatively closed system and it is suggested that the amount, the type, and the timing of the observed teaching/learning processes suffice to explain the phenomena and products of first language acquisition. (GO)
ERIC Note: Portions of this paper were presented at the Biennial Meeting of the Society for Research in Child Development (Denver, Colorado, April 10-13, 1975).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Language; Infants; Interaction Process Analysis; Language Acquisition; Language Instruction; Language Learning Levels; Mothers; Parent Child Relationship; Verbal Communication; Speeches/Meeting Papers